2012
DOI: 10.5194/bg-9-2973-2012
|View full text |Cite
|
Sign up to set email alerts
|

Response of <i>Nodularia spumigena</i> to <i>p</i>CO<sub>2</sub> – Part 1: Growth, production and nitrogen cycling

Abstract: Abstract. Heterocystous cyanobacteria of the genus Nodularia form extensive blooms in the Baltic Sea and contribute substantially to the total annual primary production. Moreover, they dispense a large fraction of new nitrogen to the ecosystem when inorganic nitrogen concentration in summer is low. Thus, it is of ecological importance to know how Nodularia will react to future environmental changes, in particular to increasing carbon dioxide (CO2) concentrations and what consequences there might arise for cycl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 69 publications
4
60
1
Order By: Relevance
“…(Sivonen et al, 1989;Finni, 2001;Vahtera et al, 2005). Calm conditions, a salinity of 7-8, temperatures >16 • C, and a N : P ratio <8 promote the formation of extensive Nodularia blooms in the sea surface layer (Wasmund, 1997). Degerholm et al (2006) suggested that Nodularia sp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Sivonen et al, 1989;Finni, 2001;Vahtera et al, 2005). Calm conditions, a salinity of 7-8, temperatures >16 • C, and a N : P ratio <8 promote the formation of extensive Nodularia blooms in the sea surface layer (Wasmund, 1997). Degerholm et al (2006) suggested that Nodularia sp.…”
Section: Introductionmentioning
confidence: 99%
“…Since nitrogen fixation rates are supposed to increase under higher CO 2 concentrations (Wannicke et al, 2012) additional P (or changing C : N : P ratios) are required. This will be studied as part of two other investigations based on the same experimental setup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this has been challenged by Liu et al (2010). For example, there is evidence that some functions such as nitrogen fixation (Wannicke et al, 2012), nitrification and bacterial activity are influenced by changing pCO 2 levels, which would influence biogeochemical processes (summarised in Liu et al, 2010 andin Weinbauer et al, 2011). Also, there is no study on the effect of pCO 2 on specific carbon metabolism components such as BR, BGE and BCD of natural bacterial communities in aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…In the Baltic Sea, several studies of CO 2 effects have been undertaken on the organism level of fish (Frommel et al, 2013), zooplankton (Pansch et al, 2012;Vehmaa et al, 2012), macrophytes (Pajusalu et al, 2013), benthic species (Hiebenthal et al, 2013;Stemmer et al, 2013), and filamentous cyanobacteria (Czerny et al, 2009;Eichner et al, 2014;Wannicke et al, 2012). Studies on the impacts of elevated CO 2 at the ecosystem level, however, have thus far been limited to Kiel Bight in the western Baltic Sea (Engel et al, 2014;Rossoll et al, 2013;Schulz and Riebesell, 2013), which may fundamentally differ from other parts of the Baltic Sea.…”
Section: Introductionmentioning
confidence: 99%